Integrating models of cognition and culture will require a bit more math. (28th May 2020) - Zefferman, Matthew R.; Smaldino, Paul E.
Abstract: We support the goal to integrate models of culture and cognition. However, we are not convinced that the free energy principle and Thinking Through Other Minds will be useful in achieving it. There are long traditions of modeling both cultural evolution and cognition. Demonstrating that FEP or TTOM can integrate these models will require a bit more math.